Revisão sistemática dos Octocorallia (Coelenterata, Anthozoa) dos recifes de Abrolhos, BA, Brasil - Castro, Clovis Barreira e (1986)
Systematic studies were developed on shallow water Octocorallia (Coelenterata, Anthozoa) from the Abrolhos area, Bahia, Brazil. These studies were based on material from collections in Brazilian and American institutions. The specimens from Abrolhos were compared with specimens of other localities to determine the variation ocurring within each species. Sclerites of every species were illustrated; most using Scanning Electron Microscopy (SEM). Six species were reported: Carijoa riisei (Duchassaing & Michelotti, 1860); Muriceopsis sulphurea (Donovan, 1825); Plexaurella grandiflora (Verrill, 1912); Plexaurella sp.; Olindagorgia gracilis (Verrill, 1912); e Phyllogorgia dilatata (Esper, 1806). Four of these species (P. grandiflora, Plexaurella sp., Q. gracilis e P. dilatata) are endemic in Brazilian territory and two (Plexaurella sp. e Q. gracilis) occur only in the Abrolhos area. The description of each species includes synonyms, type depository, type locality and geographical distribution.